Analysis of Risk Factors for Anemia in Pregnant Women in the Sebabi Health Center Working Area - Multiansyah, Multiansyah; Noor, Meitria Syahadatina; Fujiati, Fujiati; Suhartono, Eko; Musafaah, Musafaah (Journal La Medihealtico, 2024)
The prevalence rate of anemia among pregnant women in East Kotawaringin Regency in 2021 was 14%, in 2022 it decreased to 13.7% and in 2023 it increased to 16%. To determine the relationship between the incidence of anemia in pregnant women at Sebabi Health Center. The study was analytical observational using a cross sectional approach with a population of 300 people, 83 people were obtained as samples using proportionate random sampling technique. The research instrument was a questionnaire. The dependent variable: anemia. Independent variables: age, parity, knowledge, attitude, culture, education level and income. Bivariate analysis using chi square and multivariate using multiple logistic regression. The results showed there was a relationship between parity (p=0.000), knowledge (p=0.000), culture (p=0.004), and education level (p=0.000) while there was no relationship between age (p=0.174) attitude (p=0.147), and income (p=0.176) with the incidence of anemia in pregnant women. Parity was most associated with the incidence of anemia among pregnant women (exp(B)=10.061). There is an association between culture, parity, knowledge, education level and no association between age, parity, and income with anemia incidence. The parity variable is the most associated with the incidence of anemia among pregnant women.